Effect of light during broiler mothers’ eggs incubation on embryos growth and hatched chicks weight - العيسى بشرى; القاضي زينب (Latakia University Journal -Biological Sciences Series, 2022)
To study the importance of adding LED light to the artificial incubation process, and the extent of broiler embryos response to some lighting systems, and to assess the extent of the impact of these systems on both embryonic development, and the quality of hatched chicks, and some hatching standards, a study was conducted on 315 fertilized egg of hybrid broiler mothers’ (Hubbard FLEX), where the eggs were randomly divided into three different treatments according to the lighting system applied during incubation (continuous darkness 0L:24D, 12hours of light versus 12hours of darkness 12L:12D, continuous light 24L:0D), with 105 eggs for one treatment, and the single treatment was divided into three replicates by 35 eggs per one, at the same incubation and post-hatching conditions for all treatments. The results showed a significant increase (P<0,05) in weight average weight of embryos during days 7,11 and 19 of incubation, as this mean for treatment T2(12L:12D) reached (0.55, 4.22, 20.63)g respectively, compared with treatments T1(0L:24D ( (0.35, 3.42, 19.79)g and T3(24L: 0D) (0.25, 3.14, 19.18)g, in addition to the superiority of treatment T2(12L:12D) in the percentage of hatching and chicken hatchability (72.09, 54.28)% over treatments T1(0L:24D) (57.40, 34.91)% and T3(24L: 0D) (49, 32.06)%, the least incubation period was in T2(12L:12D) (489.3)h, followed by treatment T3(24L: 0D) (492)h, then treatment T1(0L:24D) (493.8)h. The lowest rates of early and late and total embryonic mortality were observed in treatment T2(12L:12D) (0, 5.73, 11.32)%, with no significant differences between T1(0L:24D) and T3(24L:0D), In addition to the absence of a significant difference in the middle mortality between the three treatments, the superior weights of the newly hatched and one-week-old chicks were in treatment T2(12L:12D) (38.11, 156.5)g compared with the chicks of the treatments T1(0L:24D) (36.08, 151.1)g and T3(24L: 0D)(34.71 ,151.6)g, these results showed the importance of application an alternating light and dark system 12L:12D and the role of this in improving the incubation process and the quality of the hatched chicks.